Pearson discover history student book 3 - Tol, David Van; Ottery, Sharon (Pakistan : Pearson (Kifayat Publishers), 2024)
Pearson Discover History 3 continues the series by exploring later historical periods and significant global developments. Through detailed narratives, timelines, maps, and interactive activities, it examines major events, influential leaders, and social changes that shaped the modern world. The book encourages critical thinking, connects past events to present-day contexts, and strengthens students$1 (Bskills in historical analysis and interpretation.s
Keywords: History - Text Book